Personal and National Narratives: Systemic Functional Linguistic Analysis of 'I' and 'We' in the Biden’s Presidential Campaign - Habiba Al Umami (CV. Creative Tugu Pena, 2024)
This study delves into Joe Biden's use of the personal pronouns